ANALISIS EFEKTIVITAS INVENTORY CONTROL INSTALASI FARMASI RUMAH SAKIT AISYIYAH PONOROGO DENGAN METODE ABC VEN - Sawitri, Satwika Budi; Zumaroh, Macfudza Anil; Fitrian, Ahyana; Al Hasanah, Fauziyyah (Jurnal Ilmiah Global Farmasi (JIGF), 2025)
Drug supplies are important and must be considered so as not to cause losses to hospitals that will have an impact on services to patients. To process and control inventory, ABC VEN analysis is one method that can be used to determine the priority of appropriate drugs based on their cost and therapeutic effects. The purpose of this study was to determine the application of the ABC VEN method in determining the maximum stock at the "X" Hospital Pharmacy Installation in Ponorogo and determine the effectiveness of the application of the method. This research method is descriptive, qualitative and quantitative. By using data on hard drugs from August to October 2023. Data is processed using the ABC method by calculating investment value, residual value, critical value and ITOR value. The average return obtained on the investment value is Rp. 1.303.802.308,86, the average return on the residual value is Rp. 483.652.969,57. While the ITOR result is 1.49. The conclusion of the ABC analysis is not well applied, this is evidenced by the increasing investment value but there is still a lot of unused drugs left. The ITOR value is considered inefficient because it is less than the ITOR efficient value, which is 8-12.